PENERJEMAHAN KOSA KATA BUDAYA PADA BUKU TEKS INFORMASI PARIWISATA BALI UNTUK GUIDE JEPANG - Sendra, I Made (Jurnal Analisis Pariwisata, 2016)
Japanese and Balinese culture have a lot of similarities especially on the nomenclature of cultural terms. Accordingly, it is very important to know the cross-cultural understanding in cultural terms of Balinese language and Japanese language. This article highlight the translation procedure of cultural terms from Balinese language to Japanese language.The article utilized the theory of functional equivalence from Nida and Teber and analysis of meaning component from Newmark. This analysis is aimed to get a closer approximation of meaning by comparing the di erences and the similarities between Balinese and Japanese cultural terms. The result shows that the functional equivalence in translation could be attained by applying the parallel dichotomous symbolism approach. This approach is applied by comparing the di erences and the similarities of the form and the function of cultural symbols which is embodied on cultural terms.